(untitled) (Revista de Ciências Agroveterinárias, 2009)
The castor-bean (Ricinus communis L.) is a species with high oil production potential. Consequently, it is a very important crop for the Brazilian Program for Biodiesel. The objective of this study was to evaluate the agronomic performance of castor bean genotypes, at different sowing dates, in the plateau of Santa Catarina State, southern Brazil. The experiment was set in the city of Lages, during the growing season of 2006/07. Three sowing dates were tested: 11/03, 11/ 23 and 12/13. A split-plot randomized block was used as experimental design, with two replications per treatment. The following traits were evaluated: vegetative cycle, total cycle, plant height, first insertion raceme height, colon diameter, relationship seed-hulls, mass of a thousand seeds and grain yield. The interaction between genotype and sowing date affected vegetative cycle, total cycle and first insertion raceme height. Grain yield of all tested genotypes decreased with the delay in sowing date. The highest grain yield (1,500 kg ha-1) was obtained when sowing was performed in the beginning of November. Further studies, including new genotypes and a wider range of sowing dates, are necessary to determine the best castor bean sowing period in the high lands of Santa Catarina.